Using Stake's Qualitative Case Study Approach to Explore Implementation of Evidence-Based Practice. (September 2013) - Boblin, Sheryl L.; Ireland, Sandra; Kirkpatrick, Helen; Robertson, Kim
Although the use of qualitative case study research has increased during the past decade, researchers have primarily reported on their findings, with less attention given to methods. When methods were described, they followed the principles of Yin; researchers paid less attention to the equally important work of Stake. When Stake's methods were acknowledged, researchers frequently used them along with Yin's. Concurrent application of their methods did not take into account differences in the philosophies of these two case study researchers. Yin's research is postpositivist whereas Stake's is constructivist. Thus, the philosophical assumptions they used to guide their work were different. In this article we describe how we used Stake's approach to explore the implementation of a falls-prevention best-practice guideline. We focus on our decisions and their congruence with Stake's recommendations, embed our decisions within the context of researching this phenomenon, describe rationale for our decisions, and present lessons learned.